Correlation of hs-CRP with in-hospital Outcome of Patients with Acute Coronary Syndrome (ACS) - Alam, Muhammad Khurshed; Awal, Anisul; Nahid, Salma; Akbar Chowdhury, Sharif Mohammad Muizzul; Mamun, Kazi Shamim Al; Morshed, AKM Manzur (Bangladesh Heart Journal, 2022)
Background and Objectives: Coronary artery disease (CAD) is a worldwide health epidemic. Acute coronary syndrome (ACS) is a potentially life-threatening condition of CAD. Serum high-sensitivity C Reactive Protein (hs- CRP) is being increasingly used as a marker for cardiac risk assessment and as a prognostic tool in acute coronary syndrome. The objective of this study was to evaluate the prognostic value of hs-CRP in predicting cardiovascular outcome in patients presenting with acute coronary syndromes. Methods: This prospective observational study was carried out in the department of cardiology of Chittagong Medical College Hospital (CMCH), Chittagong, from April 2013 to March 2014. Total 100 patients presenting with acute coronary syndromes who fulfilled the selection criteria were included in the study. Serum hs-CRP of all patients was assayed on admission and study population divided into 4 groups according to hs-CRP quartiles. All four groups were followed-up till discharge and occurrence of any cardiovascular events were sought. Results: Mean hs-CRP was 18±2.9mg/L (mean±SD), ranged from 1.6 mg/L to 71.2 mg/L /L. The mortality was significantly higher in quartile-4 (7%, p-0.001) and quartile- 3 (4%, 0.005) as compared to quartile-1 and 2 (0% and 2% respectively). 12% patients developed heart failure in quartile-4 vs 2% in quartile-1 (p-0.045). Similarly other cardiac complications like cardiogenic shock, arrhythmias and heart blocks occurred in increasing frequency among patients of higher quartiles. Conclusions: Elevated hs-CRP is a predictor of adverse outcome in patients with acute coronary syndromes and helps in identifying patients who may be at risk of cardiovascular complications. Bangladesh Heart Journal 2022; 37(1): 34-39